The Effect Of Banana Blossom Consumption On Increasing Breast Milk Production In Public Mothers At Murniati Clinic Kisaran - Atika Pohan; Juliana Margolang (Science Midwifery, 2022)
Breast milk is the first and foreive food that is best for babies. The thing that needs to be consideres by post partum mother giving breast milk to the baby is by consuming fruit and vegetables that can increase the amount of breast milk. Banana Blossom contains lactogogum which has performance stimulating oxytocin and prolactin hormones such as alkaloids, polyphenols, steroids, flavonoids, which are effective in increasing breast milk production. In this case, researchers conducted nonpharmacological studies such as Banana Blossom consumption. This research aims to find out the effect of Banana Blossom consumption on increased breast milk production in post partum in Clinic Muriati Kisaran. The method used is the Quasi eksperiment method with the research design of one group pretest postest. The samples in this study were as many as 20 post partum in clinik murniati kisaran, using total sampling techniques. Data collection is carried out in the form of observation. The statistical test used is the t test. The results showed that there was an influence increase in breast milk production in post partum mothers after consuming banana blossoms with a value of P-Value of 0,012 < 0,05. Based on the results of the study, the increase in breast milk production in the mother occurred because the content found in the heart of bananas is lactogogum which has the performance of stimulating oxytocin hormones and prolactin alkaloids, polyphenols, steroids, and flavonoids in increasing the production of breast milk.